KOMPETENSI PEGAWAI PADA DINAS PENDIDIKAN KOTA PEKANBARU - Citra, Silvia; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Competence in the education office of the city of Pekanbaru from the phenomenon is that there are still many employees who lack educational back ground with placements that are not in accordance with their fields. The purpose of this study was to determine the factors that influence the competence of employees in the education office of the city of Pekanbaru and the competence of employees in the education office of the city of Pekanbaru. The method used in this study is a qualitative method that uses descriptive data analysis, namely analysis that seeks to provide a detailed description based on the facts founds in the field regarding the formulation of the problem, in supporting work results based on the results of interviews which conclusions will be drawn. The results of the study indicate that the competence of employees in the education office of the city of pekanbaru is generally quite good. When viewed based on the dimension of knowledge of indicators that have not been fully implemented, namely knowledge possessed by employees who handle their work in the education office of the city of Pekanbaru. The dimensions of this attitude there are indicators that have not run according to expectations, namely the education office staff in the city of Pekanbaru in response to each complaint.            Keywords: competence,Education,Attitude,Knowledge